2011
DOI: 10.1002/app.33610
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance properties of graphite oxide/poly(3,4‐ethylene dioxythiophene) composites

Abstract: Poly(3,4‐ethylene dioxythiophene) (PEDOT) and graphite oxide (GO)/PEDOT composites (GPTs) doped with poly(sodium styrene sulfate) (PSS) were synthesized by in situ polymerization in aqueous media. The electrochemical capacitance performances of GO, PEDOT–PSS, and GPTs as electrode materials were investigated. The GPTs had a higher specific capacitance of 108 F/g than either composite constituent (11 F/g for GO and 87 F/g for PEDOT–PSS); this was attributable to its high electrical conductivity and the layer‐wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…Compared with the spectra of the pure MWCNT, the appearance of C]O stretching vibration peak of the carboxylic group at 1705 cm À1 confirms the carboxylic functionalization of the MWCNTs in the MWCNTseCOOH spectrum [30]. For the PEDOT/Cl spectrum, the vibrations around 1350 and 1520 cm À1 originate from the quinoid structure and stretching modes of CeC and C]C in the thiophene ring, respectively [31]. Vibrations at 1206, 1144, 1089, and 1053 cm À1 are attributed to stretching of the CeOeC bond in the ethylenedioxy group, peak at 926 cm À1 is ascribed to the ethylenedioxy ring deformation mode, and the vibration modes of the CeS bond in the thiophene ring are observed at 692, 843 and 980 cm À1 [32e34].…”
Section: Ft-ir Spectroscopymentioning
confidence: 52%
See 1 more Smart Citation
“…Compared with the spectra of the pure MWCNT, the appearance of C]O stretching vibration peak of the carboxylic group at 1705 cm À1 confirms the carboxylic functionalization of the MWCNTs in the MWCNTseCOOH spectrum [30]. For the PEDOT/Cl spectrum, the vibrations around 1350 and 1520 cm À1 originate from the quinoid structure and stretching modes of CeC and C]C in the thiophene ring, respectively [31]. Vibrations at 1206, 1144, 1089, and 1053 cm À1 are attributed to stretching of the CeOeC bond in the ethylenedioxy group, peak at 926 cm À1 is ascribed to the ethylenedioxy ring deformation mode, and the vibration modes of the CeS bond in the thiophene ring are observed at 692, 843 and 980 cm À1 [32e34].…”
Section: Ft-ir Spectroscopymentioning
confidence: 52%
“…5a. It can be seen that the three types of electrodes show a vertical trend at low frequencies region, indicating the capacitive behavior according to the equivalent circuit theory [41], no or negligible semicircle observed at high frequency region for the three types of electrodes is ascribed to the low interfacial charge-transfer resistance as their high conductivity of films [31]. The equivalent series resistance (ESR) can be obtained from the intersection of the curve at the xaxis, it mainly arises from the electrolyte, the intrinsic resistance of the active material, and the contact resistance at the active material/current collector interface [38].…”
Section: Electrochemical Propertiesmentioning
confidence: 90%
“…The peaks observed at 1413 and 1235 cm À1 represent the OeH deformation and CeOH stretching vibration, in addition, the peak at 1055 cm À1 is the characteristic peak of epoxide group [36]. For the pure PEDOT spectrum, the vibrations around 1350 and 1518 cm À1 are attributed to the quinoid structure and stretching modes of CeC and C]C in the thiophene ring, respectively [37]. Vibrations at 1203, 1144, 1089, and 1058 cm À1 originate from stretching of the CeOeC bond in the ethylenedioxy group [38].…”
Section: Compositions and Structuresmentioning
confidence: 95%
“…The impedance plots of two types of electrodes are featured by a vertical trend at low frequencies, indicating capacitive behavior according to the equivalent circuit theory [50], and the straight line in the low frequency for PEDOT/SDS-GO electrodes lean more towards imaginary axis, manifesting that they have better capacitive character. In addition, a semicircle at high frequency is not detected for the two types of electrodes, which is attributed to the low interfacial charge-transfer resistance because of their high conductivity of films [37]. Another important information can be obtained from the plots at higher frequencies is the knee frequency, beyond which the capacitive behavior is replaced by the more inclined diffusion line, and the higher knee frequency means the lower diffusion impedance and faster charge transfer rates [50].…”
Section: Electrochemical Propertiesmentioning
confidence: 97%
“…Almost all potential cycling stability studies of different types of PEDOT films have been conducted in three‐electrode cells 1731. It was shown that the cyclic voltammogram (CV) of PEDOT‐PSS was stable for 400 potential cycles (−0.9–0.5 V vs. SCE) except of changes occurring during the first cycles 18, while PEDOT‐PSS retained 66 % of its initial capacitance during 1200 cycles between −0.2–0.8 V (vs. SCE) 20. The composite film of PEDOT, graphite oxide and PSS had a slightly better stability by retaining 78 % of the capacitance during 1200 cycles in the same potential interval 20.…”
Section: Introductionmentioning
confidence: 99%